PENGARUH IMPLEMENTASI RELATIONSHIP MARKETING TERHADAP TINGKAT KEPUASAN PASIEN DI RUMAH SAKIT UMUM “YAKKSI” GEMOLONG SRAGEN - Budhi Poniman (STIE AUB Surakarta, 2013)
This study aimed to determine the effect of relationship marketing strategy that consists of understanding the expectation of patients, formed a partnership with the patients, employees empowerment and total quality management on the level of satisfaction of patients hospitalized